The Influence of Training on Financial Statement Preparation on Entrepreneurship Performance (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to examine the effect of financial report preparation training on entrepreneurial performance at UMKM Guided by the West Java Chamber of Commerce in Bandung. The research method applied is in the form of a descriptive analytical survey method, while the sample used is 32 respondents. The variables studied from each respondent were training in the preparation of financial reports and entrepreneurial performance. The type of data collected is primary data. The results of the study identified that training in preparing financial reports was no significant on entrepreneurial performance. The object of this research is that the sample of respondents used is still limited to the UMKM assisted by the West Java Chamber of Commerce in Bandung, therefore it is necessary to carry out further research based on more varied sampling with a longer duration, in order to obtain generalizable results.